2006
DOI: 10.1136/ard.2005.046540
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma levels of fat-derived hormones adiponectin, leptin, resistin and visfatin in patients with rheumatoid arthritis

Abstract: Background: Rheumatoid arthritis is a chronic autoimmune inflammatory condition characterised by polyarthritis and severe change in body mass and neuroendocrine environment. Objectives: To investigate plasma levels of adipocytokines (leptin, adiponectin, visfatin and resistin) in patients with rheumatoid arthritis and to compare them with levels in healthy controls. Methods: Adiponectin, resistin, visfatin and leptin concentrations were measured in 31 patients with rheumatoid arthritis and 18 healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
408
7
19

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 479 publications
(460 citation statements)
references
References 20 publications
26
408
7
19
Order By: Relevance
“…57,72 Serum levels of leptin have generally been reported to be higher in patients with RA than in control subjects. 70,71,73 Bokarewa et al also observed that circulating plasma concentrations of leptin were significantly higher than matched synovial fluid sample leptin levels. Local consumption of leptin in the joint cavity was associated with nonerosive joint disease, suggesting that leptin has a protective role against the destructive course of RA.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 98%
See 1 more Smart Citation
“…57,72 Serum levels of leptin have generally been reported to be higher in patients with RA than in control subjects. 70,71,73 Bokarewa et al also observed that circulating plasma concentrations of leptin were significantly higher than matched synovial fluid sample leptin levels. Local consumption of leptin in the joint cavity was associated with nonerosive joint disease, suggesting that leptin has a protective role against the destructive course of RA.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 98%
“…70,71 In these subjects, it has been reported that acute fasting induces an improvement of different clinical and biological measures of disease activity associated with a fall in circulating leptin, which is related to CD4 lymphocyte hyporeactivity and increased IL-4 secretion. 72 However, the same investigators showed that after a 7-day ketogenic diet in patients with RA, there were no significant changes in any clinical or biological measurements of disease activity, despite a significant increase in serum leptin concentrations.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 99%
“…Leptin concentrations were found to be similar [12,13,14,15,16], lower [17], or higher [18,19] in comparison with healthy controls or with pts with osteoarthritis (OA) [20]. Plasma levels of adiponectin, leptin and visfatin were found to be increased in RA pts [21] or did not differ significantly in RA pts and in healthy controls [22].…”
Section: Introductionmentioning
confidence: 99%
“…This idea is underpinned by several in vivo and in vitro findings: in RA patients, circulating leptin levels have been found to be higher than in healthy controls (33,34); however, other studies reported unchanged levels. Low leptin levels associated with food restriction have been linked to CD4ϩ lymphocyte hyporeactivity and increased interleukin-4 (IL-4) secretion (35).…”
Section: Leptin and Rheumatic Diseasesmentioning
confidence: 99%
“…Adiponectin has been found to be higher in RA patients than in healthy controls (34,(77)(78)(79)(80)(81). Moreover, adiponectin levels are increased in early RA patients that had never taken disease-modifying antirheumatic drugs and in chronic RA patients (82).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 99%